Komunikasi Pemerintahan dalam Penanggulangan Bencana Banjir Bandang di Masamba Kabupaten Luwu Utara - Dandi Darmadi (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2021)
This study discusses government communication in disaster management in Masamba, North Luwu Regency, South Sulawesi Province. The purpose of this study was to describe the communication process of the North Luwu Regency Government, South Sulawesi Province in handling banjir bandang disasters in Masamba. This research method uses a qualitative descriptive approach. The results of the study indicate that the central government's efforts in disaster management focus on handling refugees and restoring housing and public facilities. However, in government communication that occurred in the Masamba flash flood, North Luwu Regency, South Sulawesi Province, the central government was less communicative, causing several problems such as the utilization of volunteers and the distribution of logistics was uneven and less focused. This is evidenced by the rejection by the central government through the Minister of Human Development and Culture regarding the construction of temporary shelters initiated by the Indonesian National Armed Forces (TNI) from the Hasanuddin Military Command not utilized even though the construction has been completed. Finally, the Regent of North Luwu with a humanistic approach was able to resolve the problem between the community and the central government